Butterworths financial services compliance manual (Butterworths, 1988)
Butterworths Financial Services Compliance Manual provides a guide in implementing a form of internal control in accounting to ensure compliance with the Financial Services Act of 1986. The manual is organized into 11 parts; each part tackles a specific area of concern in the implementation of the Act.